Phylogeography of the giant honey bees based on mitochondrial gene sequences - Bhatta, Chet P.; Zajonz, Sarah C.; Smith, Deborah R. (Frontiers in Bee Science, 2024)
Our goal was to resolve phylogenetic relationships among Apis laboriosa, and the Apis dorsata subspecies A. d. dorsata, A. d. binghami, and A. d. breviligula, the last two of which have been proposed as full species by several authors. We carried out a phylogenetic analysis of the giant honey bees using mitochondrial cox1 and cox2 gene sequences analyzed with maximum likelihood methods. We obtained strong support for four clades within A. dorsata in the broad sense: the three subspecies or species mentioned above, and a fourth lineage from south India. However, our analysis did not resolve the phylogenetic relationships among the four lineages. The presence of two genetically distinguishable groups of “A. dorsata” in India parallels the presence there of two cavity-nesting honey bees, A. cerana cerana and A. c. indica (the black hill bees and yellow plains bees, respectively). This suggests that past climatic or geological events may have temporarily isolated Indian populations from populations of the Asian mainland, leading to divergence and possibly speciation of Indian giant and cavity-nesting bees, followed by recolonization of India by eastern Asian forms. Recognition of these distinct lineages is important for conservation planning, so that their individual distributions, ecologies, and migration patterns can be considered, and so that the genetic diversity they represent can be maintained.